IMPLEMENTATION OF NATIONAL DEFENSE POLICY: MANAGEMENT OF INDONESIA’S RESERVE COMPONENTS - Shobri, Taufiq; yusgiantoro, purnomo; Navalino, Djoko A; sutanto, sutanto (Fakultas Politik Pemerintahan IPDN, 2024)
Abstract This research is rooted in the increasing need for an effective and comprehensive national defense system in Indonesia, particularly in light of the dynamic and evolving security environment. In recent years, Indonesia has faced a wide range of threats, both traditional and non-traditional, including territorial disputes, terrorism, and cyber threats. These challenges require the Indonesian National Armed Forces (TNI) to maintain a high level of readiness and flexibility in their defense operations. The result revealed the strategic role of Komcad in enhancing the capacity of the Indonesian National Armed Forces (TNI) to safeguard national sovereignty and respond to emerging threats. The formation, recruitment, selection, and training processes for Komcad are explored in the context of Indonesia’s comprehensive defense system, which integrates all national resources to maintain security. Additionally, the study evaluated the legal framework governing the Reserve Components, the challenges in their implementation, and the strategic importance of Komcad in supporting national defense. Drawing on a literature review and qualitative research, this analysis provides insights into the operational readiness of Komcad and its potential contributions to Indonesia’s future defense strategy. Keywords: defense policy, reserve components, human resource management, and national defense systems.